Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1996
DOI: 10.1093/oxfordjournals.molbev.a025610
|View full text |Cite
|
Sign up to set email alerts
|

The impact of population expansion and mutation rate heterogeneity on DNA sequence polymorphism

Abstract: In order to study the effect of mutation rate heterogeneity on patterns of DNA polymorphism, we simulated samples of DNA sequences with gamma-distributed nucleotide substitution rates in stationary and expanding populations. We find that recent population expansions and mutation rate heterogeneity have similar effects on several polymorphism indicators, like the shape and the mean of the observed pairwise difference distribution, or the number of segregating sites. The inferred size of population expansion thu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
220
0
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 377 publications
(243 citation statements)
references
References 33 publications
16
220
0
1
Order By: Relevance
“…The results demonstrated that S. crosnieri populations had different demographic histories in vent and cold seep environments. Significant D values may be due to factors such as population expansion and bottleneck (ArisBrosou and Excoffier 1996). The significant negative D values for the entire vents dataset also could support the results.…”
Section: Discussionmentioning
confidence: 99%
“…The results demonstrated that S. crosnieri populations had different demographic histories in vent and cold seep environments. Significant D values may be due to factors such as population expansion and bottleneck (ArisBrosou and Excoffier 1996). The significant negative D values for the entire vents dataset also could support the results.…”
Section: Discussionmentioning
confidence: 99%
“…A low genomic evolutionary rate and elevated inbreeding frequency may have contributed to the low genetic variation observed in this population. Demographic analyses (Tajima's D) using mtDNA sequence polymorphism showed a signal of population expansion in the Kuchi population characterized by an excess of rare variants consistent with population growth (Tajima, 1989;Aris-Brosou & Excoffier, 1996;Schmidt & Pool, 2002;Johnson et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…While changes in population size do affect the relationship between effect size and mutation frequency [48][49][50][51][52][53][54][55][56][57][58][59][60][61] (Fig 1 and S5 Fig), different mappings of genotype to trait value do this in radically different ways for the same demographic history (Fig 1). From an empirical perspective, our findings suggest that re-sequencing in large samples is likely the best way forward in the face of the allelic heterogeneity imposed by the presence of rare alleles of large effect.…”
Section: Resultsmentioning
confidence: 99%
“…The increase in the number of rare alleles due to population growth is a well established theoretical and empirical result [48][49][50][51][52][53][54][55][56][57][58][59][60][61]. The exact relationship between rare alleles [4,17,26,62,63], and the demographic and/or selective scenarios from which they arose [21,22,64], and the genetic architecture of common complex diseases in humans is an active area of research.…”
Section: Additive and Dominance Genetic Variance In The Populationmentioning
confidence: 99%
See 1 more Smart Citation